CLIPPINGS AND ORIGINAL WORDS - Maxammadjonova Raximaxon; Xaydarova Nigora (TADQIQOTLAR, 2025)
Abstract: Clipping, the process of shortening words by removing syllables or letters, is a prevalent phenomenon in language evolution. This study investigates the role of clippings in linguistic economy and semantic shifts within the English language. Through a corpus-based analysis of contemporary English texts, we identify common clipping patterns and examine their impact on language efficiency and meaning. The findings suggest that clippings contribute to linguistic economy by reducing syllable count and facilitating quicker communication. Additionally, clippings often undergo semantic shifts, acquiring new meanings or connotations distinct from their original forms.  This  research  highlights  the  dynamic  nature  of  language  and  the  adaptive strategies employed by speakers to enhance communication efficiency.